A FORMAÇÃO PROFISSIONAL DE EDITORES NO DIÁRIO DOS CAMPOS E NA GAZETA DO POVO - Silva, Gisele Barão da (2015)
This research characterises the upbringing of the journalists who perform editing functions at Parana’s regional printed newspapers “Diário dos Campos” in Ponta Grossa and “Gazeta do Povo” in Curitiba, in order to identify their academic training and the knowledge of their daily practices. For this object’s analysis, the knowledge involving Journalism and Journalistic Editing, the Brazilian Press’ modernization – time in which Editing positions gain more strength – the editor’s competences and the academic training in Journalism, specifically in Journalistic Editing, are discussed. Theoretical background include the concept of theoretical and action knowledge, news-value, Organizational and “Gatekeeping” theories. The methodology presents bibliographic and documental research as well as the performance of questionnaires and interviews. This dissertation shows that the editing activity is made of competences related to Journalism deontology and their development within the market. It also shows that Journalism Courses in Paraná have a curriculum based on forming, mostly, news reporters and do not leave room for the teaching of editing techniques.